Answer:
[tex](x+4)^2 + (y-3)^2 + (z+2)^2 - 3^2 = 0[/tex]
Step-by-step explanation:
You have to find a, b, c, r so that the polynomial expands to match the given equation.
[tex](x-a)^2 + (y-b)^2 + (z-c)^2 - r^2 =\\x^2-2ax+a^2+\\y^2-2by+b^2+\\z^2-2cz+c^2-r^2 =\\ x^2 + y^2 + z^2 + 8x - 6y + 4z + 20[/tex]
[tex](a^2+b^2+c^2-r^2-20)+\\x(-8-2a)+y(6-2b)+z(-4-2c)=0[/tex]
[tex]-8-2a=0, 6-2b=0, -4-2c=0\\a=-4, b=3, c=-2[/tex]
[tex](-4)^2+3^2+(-2)^2-r^2-20 = 0[/tex]
[tex]16+9+4-20=r^2[/tex]
[tex]r^2=9[/tex]
[tex]r=3[/tex]
[tex](x+4)^2 + (y-3)^2 + (z+2)^2 - 3^2 = 0[/tex]